Il-17 Family Cytokines in Psoriasis: Radioactive Splendor Dual Role in Inflammation and Tissue Re Modeling - Adnan ALI, Hiyam; Al aaraji , Ali; Tareq sharara, Dina (Libyan Journal of Medical and Applied Sciences, 2026)
Psoriasis is an immunologically mediated distressed skin disease of chronic tendency that is correlated to the over proliferation of keratinocytes and chronic inflammation. IL-17A is a known therapeutic target but IL-17 cytokine family (as IL-17F, IL17C and IL-17E) can also mediate the inflammation and structural reorganization of psoriatic skin.To study the dual function of IL-17 family cytokines to regulate inflammatory reactions and tissue remodeling in psoriasis, and their relationship with clinical severity. The case-control study design was used, and 100 patients with moderate- to severe plaque psoriasis and 100 healthy controls matched according to 12 age-matched design factors were included. ELIZA measure of serum cytokine concentrations (IL-17A, IL-17F, IL-17C, IL-17E, TNF- alpha and MMP-9). Haemoampicillin | qRT-PCR was applied to analyze gene expression of lesional and non-lesional skin biopsies. To evaluate the effects of IL-17 cytokines on human primary keratinocytes, primary keratinocytes were stimulated in vitro with IL-17 cytokines and the effects on proliferation and inflammation (IL6, CXCL8, S100A9) and remodeling (MMP9, FN1, COL1A1) markers were studied. Correlation and multivariate regressions analyses were used to assess the associations with Psoriasis Area and Severity Index (PASI). All of the examined cytokines had much higher levels in the serum of psoriasis patients than controls (p < 0.05). The overexpression of IL17A, IL17F, IL17C, IL25 as well as remodeling genes status were large in lesional skin. In vitro IL-17 cytokines enhanced keratinocyte proliferation and resulted in significant upregulation of pro- inflammatory and tissue remodeling genes. The independent predictors of the PASI scores belonged to IL-17F and MMP-9. Cytokines involved in the process of inflammation and structural change were found to be clustered in a functional capture as identified through the principal component analysis. There is a dual effect of IL-17 family cytokines in the pathogenesis of psoriasis since, in addition to perpetuating inflammation, they induce remodeling of the dermis and epidermis. These results justify the need to expand treatment options beyond IL-17A inhibition and to emphasize the importance of cytokine profiling in determining the management of the disease and treatment selection.